A Nanoporous PdCo Alloy as a Highly Active Electrocatalyst for the Oxygen‐Reduction Reaction and Formic Acid Electrooxidation. Issue 11 (18th July 2013) - Xu, Caixia; Liu, Yunqing; Zhang, Huan; Geng, Haoran
Abstract A nanoporous (NP) PdCo alloy with uniform structure size and controllable bimetallic ratio was fabricated simply by one‐step mild dealloying of a PdCoAl precursor alloy. The as‐made alloy consists of a nanoscaled bicontinuous network skeleton with interconnected hollow channels that extend in all three dimensions. With a narrow ligament size distribution around 5 nm, the NP PdCo alloy exhibits much higher electrocatalytic activity towards the oxygen‐reduction reaction (ORR) with enhanced specific and mass activities relative to NP Pd and commercial Pt/C catalysts. A long‐term stability test demonstrated that NP PdCo has comparable catalytic durability with less loss of ORR activity and electrochemical surface area than Pt/C. The NP PdCo alloy also shows dramatically enhanced catalytic activity towards formic acid electrooxidation relative to NP Pd and Pd/C catalysts. The as‐made NP PdCo holds great application potential as a promising cathode as well as an anode electrocatalyst in fuel cells with the advantages of superior catalytic performance and easy preparation.